UJI KAUSALITAS GRANGER: INFLASI DAN PENGANGGURAN DI INDONESIA - Eny Setyowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
Inflation and unemployment in Indonesia are specific problems which need government attention. To overcome inflation, we must understand first some factors causing the rise of inflation, before making a policy. In relation to inflation, the number of unemployment can be influenced via company where the employees where the employees work or via manpower market.In this article the writer carried out a causality test of the relation between inflation (I) and unemployment (11) using Granger test model. In this test the writer formulated that the current inflation variable value (It) connected to past inflation and past unemployment level. The writer also tested the variable of current employment level (Ut) where current employment level is influenced by past inflation and employment levels